An approach for public cloud trustworthiness assessment based on users' evaluation and performance indicators. (17th June 2019) - Zhou, Guo-Sheng; Du, Wei; Lin, Han-Chao; Yan, Xiao-Wei
Aiming at the problem of how to quantify the trustworthiness of public cloud services, this paper proposes a method to evaluate the trustworthiness of public clouds based on users' subjective evaluations and objective monitoring values of performance indicators. According to the objective values obtained from monitoring organisations, the objective trustworthiness is calculated by using a multi-attribute decision-making method based on the ideal point (TOPSIS). Meanwhile, qualitative users evaluations are quantified by exploiting the cloud model. Finally, a comprehensive assessment of the trustworthiness of cloud service is formed based on the above results. To meet the personalised requirements, users could configure the weight of parameters included in the proposed algorithms, ranking cloud services for specific needs. Compared with other assessment algorithms, both the subjective source and objective source are taken into account, the customised weight scheme for users is provided, the model and the algorithms are designed, and a prototype is developed.